KARIR PADA ORGANISASI TANPA BATASAN (CAREER IN THE BOUNDARYLESS ORGANIZATION) - NUR HASANAH (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
“Boundaryless” is an absolute requirement for organizations attempting to get success in the twenty-first-century. Twenty-first-century business is in the midst of a social and economic revolution, shifting from rigid to permeable structures and processes and creating something new: The Boundaryless Organization (Ashkenas et al., 1995). Meanwhile, organizational restructuring (such as downsized, delayered, and outsourced many functions) attempted to be more competitive, and also the global, hypercompetition in the twenty-first-century have revolutionized careers and destroy the traditional blueprint for advancement and career success. Boundaryless careers are occupational paths that are not bounded within specific organizations but grow through project-based competency development across firms in an industry network. The rapid expansion of these processes has far outstripped our understanding of them and their influence on the structure and process of careers, with a few notable exceptions (Bridges, 1994; Saxenian, 1994; Hall et al., 1995; Arthur & Rousseau, 1996). Protean careers could be counted in the boundaryless careers since it were managed by individual. One is not bordered by strict rules as he or she was in the traditional hierarchical organizations and the traditional concept of careers. This kind of careers seems to be matched with the boundaryless organizations.